A steerable system for the RECoverable Autonomous Sonde (RECAS) to access and study subglacial lakes - M. A. Sysoev; P. G. Talalay; P. G. Talalay; X. Fan; N. Zhang; D. Gong; Y. Yang; T. Wang; Z. Deng (Geoscientific Instrumentation, Methods and Data Systems)
The study of subglacial lakes requires clean access and sampling technologies. One of the most promising alternatives is the newly developed thermal drill, the RECoverable Autonomous Sonde (RECAS), which allows downward and upward ice drilling and subglacial water sampling while the subglacial lake remains isolated from the surface. The original sonde descends downward under the force of gravity, and the borehole trajectory cannot be controlled. However, in certain cases, the sonde would preferably be able to drill at specific angles and directions, enabling it to follow a desired trajectory (e.g., maintaining verticality within the desired range) or bypass obstacles in the ice (e.g., stones and other inclusions). The general principle for the steering RECAS is to adjust the voltage for the electric thermal head heaters, which provides an opportunity to control the heat distribution on the thermal head surface, thereby altering the borehole trajectory during drilling. In this paper, the general principles of the steering RECAS are described, and experimental results on deviational ice drilling with a controllable electric thermal head are discussed.